LANGUAGE STYLES USED IN FABRIZIO ROMANO’S INSTAGRAM ACCOUNT - MARCELINO HASIHOLAN SARUMPAET; MORADA TETTY (LINGUISTICA, 2023)
This thesis examines the types, the used and the reasons why language styles used in Fabrizio Romano on his Instagram account, using Martin Joos's theory and a qualitative descriptive method.  There are five styles proposed in Joos theory. The source of data is Instagram and there were 50 captions founds as the data. Those captions in Fabrizio’s instagram were analyzed in order to classify them into their own styles. This study reveals that Fabrizio Romano uses four of five language styles in his Instagram captions: formal style (26%), casual style (40%), consulatative style (14%), and intimate style (20%). Each style has a distinct tone and communication style, with formal style indicating a formal tone and proper nouns, casual style using conversational expressions, contractions, or shortening, and consulatative style asking for advice or predictions. Intimate style conveys personal sentiments and emotions, highlighting joy and enthusiasm, and is addressed to followers based on events. The choice of language style is deliberate, with formal language maintaining professionalism and credibility, while casual and consulatative styles foster engagement and inclusivity among a diverse audience. Incorporating intimate style allows for a personal connection with followers and a sense of authenticity. Overall, these language styles work together to enhance the overall experience and success of Fabrizio Romano's Instagram account.